Differences in the coach-created psychological environment across training and competition in youth sport - Smith, N.; Quested, E.; Appleton, P.; Duda, J. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
According to achievement goal theory (AGT; Nicholls, 1989) and self-determination theory (SDT; Deci and Ryan, 2000), the psychological environment created by a coach can impact upon the quality of an athlete`s motivation and experience in sport. When the environment is more task-involving, relatedness supportive and autonomy supportive and less ego-involving, relatedness thwarting and controlling, adaptive outcomes are expected to follow. However, past work suggests that under pressure situations, leaders are more likely to adopt an interpersonal style higher in ego-involving and controlling characteristics (Mageau and Vallerand, 2003). Extending previous research, this study used an observational methodology (which captured aspects of the environment emphasised in AGT and SDT) to examine whether there were any differences in the objective psychological environment created by coaches across competitive contexts (i.e., training and matches). Method: Participants were 22 grassroots football coaches (21 males and 1 female). Coaches were filmed during a training session and match during the first 8 weeks of the season. Trained coders independently rated filmed footage in continuous 5-minute intervals, in terms of the extent to which the coach`s interpersonal style was autonomy supportive, controlling, taskand ego-involving, and relatedness supportive and thwarting. Results: Preliminary analyses suggest that during training, coaches adopt an interpersonal style that is significantly more autonomy supportive (M = 1.07, SD = 0.66) than controlling (M = 0.40, SD = 0.37), t(9) = 2.34, p = .044, and significantly more task-involving (M = 1.22, SD = 0.65) than ego-involving (M = 0.39, SD = 0.44), t(9) = 3.78, p = .004. Coach-emphasised autonomy support is significantly lower in matches (M = 0.32, SD = 0.23) than in training (M = 1.20, SD = 0.69), t(6) = 2.94, p = .026. There was a trend for controlling strategies to be emphasised more during matches (M = 1.31, SD = 0.70) than in training (M = 0.48, SD = 0.0.38), t(6) = 2.33, p = .058. Discussion: These findings suggest that competition may lead coaches to withdraw their support for autonomy, and adopt a more controlling and coercive interpersonal style. This holds negative implications for athlete motivation and has been shown to lead to more maladaptive psychosocial outcomes. To ensure children are getting the most out of sport and developing optimally, coaches should be educated to create adaptive psychological environments in training sessions and in matches.